Echocardiography in the follow-up of patients with prosthetic heart valves - KOUDELKOVÁ, E.; GROŠPIC, A.; NIEDERLE, P. (Archives of Acoustics, 1984)
In 26 patients with aortic and in 25 with mitral valve disease changes in the size, hypertrophy and function of the left ventricle (LV) within 2 years of aortic or mitral valve replacement were evaluated and compared with the preoperative echocardiographic findings.LV size decreased significantly within the first month after aortic valve replacement as well as after operation for pure or predominant mitral insufficiency. LV hypertrophy regressed in both groups of aortic valve disease. However, in patients with maximum LV dilatation and hypertrophy valve replacement failed to effect complete normalization of LV size and mass. Postoperative evaluation of LV function showed a distinct improvement in patients operated for aortic stenosis. In the groups of patients with mitral stenosis and pure aortic or mitral insufficiencies no significant change of LV function after surgery was demonstrated.Preoperative echocardiographic measurements of the LV end systolic dimension and the end systolic wall stress proved to be very useful noninvasive predictors of long-term postoperative changes of the LV function after surgical correction of the aortic or mitral valve disease.